Utilisation of optometry service at Malaysian Universities with optometry clinic / Jody Finola Joseph - Joseph, Jody Finola (2016)
Background: The World Health Organisation (WHO) has created ‘Vision 2020: The Right to Sight’ with the objective of eliminating causes of avoidable visual impairment worldwide. Utilisation of eye care services is one of the ways by which this objective can be achieved. The Optometry clinic in universities were chosen due to fulfilling the three major factors affecting utilisation namely availability, accessibility, and affordability. The Optometry clinic in Malaysian’s universities in this studies have been around for some time but there has never been a study done to assess its utilisation. Aim: The objective of this study is to know the level of utilisation of Optometry clinic in Malaysian’ local universities, to compare the level of utilisation of Optometry clinic between universities, and to identify factors affecting its utilisation. Method: This is a cross-sectional study. The total sample size calculated was 400. It is conducted through the means of questionnaires sent to a representative in each universities. A convenience sampling method is used in this study. Result: A total of 221 participants were involved in the study in which all were university students. 42.1% out of the total had utilised the service indicating a moderate level of utilisation of the universities’ Optometry clinic. Statistical analysis with Kruskal-Wallis test to compare the level of utilisation between these universities found the distribution of utilisation between all universities to be the same (0.98, P >0.05) where the significance level is P<0.05. Other than that, the factors identified to affect utilisation were awareness on the importance of eye exam (68.2%), time (61.7%), and perceived cost (30%). Conclusion: The level of utilisation of Optometry clinic in the universities were moderately good and there was no difference in level of utilisation between the universities. Factors identified to affect the clinic’s level of utilisation were awareness on the importance of eye exam, time and perceived cost.